2012
DOI: 10.1007/s10803-012-1515-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Children with Autism Spectrum Disorder Identified Within a High-Risk Infant Cohort

Abstract: Sex differences were examined in 3-year-olds with autism spectrum disorders (ASD) ascertained from a high-risk cohort, and high- and low-risk comparison groups. Participants included 319 high-risk siblings and 129 low-risk controls. Eighty-five siblings were diagnosed with ASD, including 57 of 176 boys (32.4 %) and 28 of 143 girls (19.6 %), implying a relative odds of ASD of 1.65 in boys versus girls. There were modest sex differences on cognitive and adaptive skills and ASD symptom severity at age 3, but diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
121
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 60 publications
14
121
2
1
Order By: Relevance
“…This is consistent with the idea that girls with an ASD may be under-identified because the disorder is understood to disproportionately affect males and is thus perceived as a 'male disorder' (e.g. Zwaigenbaum et al, 2012). The need for females to display more severe symptomatology to receive a diagnosis of ASD may explain the apparent paradox that in clinically diagnosed samples, females may show more severe ASD traits and comorbid psychopathology than males even though the latter have a greater vulnerability to ASD (e.g.…”
Section: Introductionsupporting
confidence: 85%
“…This is consistent with the idea that girls with an ASD may be under-identified because the disorder is understood to disproportionately affect males and is thus perceived as a 'male disorder' (e.g. Zwaigenbaum et al, 2012). The need for females to display more severe symptomatology to receive a diagnosis of ASD may explain the apparent paradox that in clinically diagnosed samples, females may show more severe ASD traits and comorbid psychopathology than males even though the latter have a greater vulnerability to ASD (e.g.…”
Section: Introductionsupporting
confidence: 85%
“…Furthermore, the available findings on the differences in clinical profiles between males and females with ASD have J Autism Dev Disord (2015) 45:2046-2055 2049 Table 1 ADOS severity score, GMDS-ER and VABS-SF at T0 and T1 Autism Dev Disord (2015) 45:2046-20552051 shown contrasting results (Carter et al 2007;Banach et al 2009;Andersson et al 2013;Van Wijngaarden-Cremers et al 2013;Hofvander et al 2009;Lugnegard et al 2011;Matson and Nebel-Schwalm 2007;Park et al 2012;Simonoff et al 2008;Lai et al 2011;Mayes and Calhoun 2011;Zwaigenbaum et al 2012;Mandy et al 2012;Szatmari et al 2012;Donna et al 2013). On the one hand, most studies found no gender differences on social behaviors or communication nor on RRB (Carter et al 2007;Banach et al 2009;Andersson et al 2013;Hofvander et al 2009;Lugnegard et al 2011;Matson and Nebel-Schwalm 2007;Park et al 2012;Simonoff et al 2008;Lai et al 2011;Mayes and Calhoun 2011;Zwaigenbaum et al 2012;Mandy et al 2012). For instance, Andersson et al (2013), in a cross-sectional study aimed at investigating gender differences in clinical and developmental profiles in 20 preschool girls and 20 age-matched preschool boys with suspected ASD, found no significant differences on communication and RRB.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies failed to find any differences in the core symptoms of ASD between males and females (Carter et al 2007;Banach et al 2009;Andersson et al 2013;Mayes and Calhoun 2011;Zwaigenbaum et al 2012;Mandy et al 2012;Szatmari et al 2012;Donna et al 2013). On the other hand, a meta-analysis of 20 studies investigating gender differences in ASD reported few differences in symptom severity between males and females.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study of over 800 families with an autistic child did not find an increased rate of ASD among first-and second-degree relatives of female ASD probands compared with males (12). Additionally, two prospective surveillance studies of the high-risk infant siblings of earlier-born ASD probands find a statistically significant effect of sibling, but not proband, sex on ASD risk on the recurrence rate for ASDs (13,14). Findings from a recent, large, twin study are similar, with only the sex of the cotwin significantly affecting recurrence rate (2).…”
mentioning
confidence: 99%